The influence of security and ease of use on purchasing decisions through the shopee application in Batam city - Muthi'ah Fitri Mas'udah; Alice Erni Husein (Trigin Publisher, 2026)
This study examines the influence of security and ease of use on purchasing decisions among Shopee users in Batam City. The research employed a causal associative quantitative approach using primary data collected through questionnaires distributed to 100 respondents selected through purposive sampling. Data analysis was conducted using SPSS version 27, including validity, reliability, classical assumption, multiple linear regression, coefficient of determination, t-test, and F-test analyses. The findings indicate that security has a positive and significant effect on purchasing decisions, as reflected by a t-value of 4.487 and a significance level of 0.001. Ease of use also demonstrates a positive and significant influence on purchasing decisions, with a t-value of 5.139 and a significance value of 0.001. Simultaneously, security and ease of use significantly affect purchasing decisions, supported by an F-value of 85.968 and a significance level of 0.001. The coefficient of determination shows that both variables explain 63.9% of the variation in purchasing decisions, while the remaining 36.1% is influenced by other factors outside the study. The results suggest that stronger application security and higher usability increase consumer confidence and convenience, thereby encouraging online purchasing decisions through the Shopee platform in Batam City.